Efficient All‐Vacuum Deposited Perovskite Solar Cells by Controlling Reagent Partial Pressure in High Vacuum. Issue 32 (25th May 2016) - Hsiao, Sheng‐Yi; Lin, Hong‐Lin; Lee, Wei‐Hung; Tsai, Wei‐Lun; Chiang, Kai‐Ming; Liao, Wei‐Yu; Ren‐Wu, Chen‐Zheng; Chen, Chien‐Yu; Lin, Hao‐Wu
Abstract : All‐vacuum‐deposited perovskite solar cells produced by controlling reagent partial pressure in high vacuum with newly developed multi‐layer electron and hole transporting structures show outstanding power conversion efficiency of 17.6% and smooth, pinhole‐free, micrometer‐sized perovskite crystal grains.